The effect of hydro-alcoholic extract of Licorice (Glycyrrhiza glabra) rhizome on the isolated Ileum of male rats and its interaction with Nitrergic system - M Farokhipour; AA Bahaoddini; E Khoshnam (Journal of Medicinal Plants, 2016)
Background: The licorice (Glycyrrhiza glabra) rhizome has been widely used in traditional medicine for treatment of gastrointestinal diseases.